Implementasi Kurikulum Merdeka Dalam Meningkatkan Motivasi Belajar Siswa Ekonomi Di Sma Muhammadiyah Bengkulu - Zufiyardi, Zufiyardi; Meirani, Meirani; Putra, Prayoga Mandala (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Research purposes This study was motivated by the low motivation of students to learn Economics which has an impact on the achievement of learning outcomes that are not optimal. Low active participation, lack of interest in the material, and disinterest in the learning process encourage the need for a more adaptive approach. The purpose of this study was to describe the implementation of the Independent Curriculum in improving student learning motivation in Economics subjects in class XI Regular of SMA Muhammadiyah 4 Bengkulu City. This study uses a qualitative descriptive approach. The subjects of the study consisted of one Economics teacher and 12 class XI Regular students who were selected purposively based on the level of participation and diversity of academic achievement. Data collection techniques were carried out through observation, in-depth interviews, and documentation of teaching materials. The research instrument was validated through expert judgment by two economics education experts. The data analysis technique used was thematic analysis with triangulation of sources and techniques. The findings showed that the implementation of the Independent Curriculum through project-based learning, differentiation, and diagnostic assessments increased student learning motivation. As many as 73% of students stated that they were more active and responsible in learning, and there was an increase in student activity scores of an average of 18% compared to the previous semester. Teachers play an important role in creating a participatory and relevant learning climate. The conclusion of this study is that the Independent Curriculum is effective in increasing student learning motivation if it is implemented consistently and adjusted to the needs of students.